The Combination of Zinc and Melatonin Enhanced Neuroprotection and Attenuated Neuropathy in Oxaliplatin-Induced Neurotoxicity - Ali M; Aziz T (Dove Medical Press, 2022)
Mayyadah Ali,1 Tavga Aziz2 1Hiwa Cancer Hospital, Sulaimani, Kurdistan Region, Iraq; 2Department of Pharmacology and Toxicology, College of Pharmacy, University of Sulaimani, Sulaimani, Kurdistan Region, IraqCorrespondence: Tavga Aziz, Tel +9647701523544, Email tavga.aziz@univsul.edu.iqObjective: The present study was designed to investigate the possible synergistic effects of melatonin with zinc in the prevention and treatment of oxaliplatin-induced neurotoxicity in rats.Methodology: Forty-eight male Wistar albino rats were used and randomly allocated into six groups: The negative control group, oxaliplatin group, zinc + oxaliplatin group, melatonin + oxaliplatin group, zinc + melatonin + oxaliplatin prevention-approach group, and zinc + melatonin + oxaliplatin treatment-approach group. The thermal nociceptive/hyperalgesia tests were performed. Brain tissue homogenate was used for measuring GFAP, NCAM, TNF α, MAPK 14, NF-kB, GPX, and SOD. Brain tissue was sent for histopathological and immunohistochemistry studies.Results: The combination therapies showed improvement in the behavioral tests. A significant increase in GPX and SOD with a significant decrease in GFAP levels resulted in the prevention approach. TNF α decreased significantly in the treatment approach. No significant changes were seen in NCAM, NFkB, and MAPK-14. The histopathological findings support the biochemical results. Additionally, immunohistochemistry revealed a significant attenuation of p53 and a non-significant decrease in Bcl2 levels in the combination groups.Conclusion: The combination of zinc with melatonin for the prevention approach was effective in attenuating neurotoxicity induced by oxaliplatin. The proposed mechanisms are boosting the antioxidant system and attenuating the expression of p53, GFAP, and TNF-α.Keywords: melatonin, zinc, oxaliplatin, neurotoxicity, antioxidant activity, GFAP, p53